Justice League. Volume 2, United order - Bendis, Brian Michael (DC Comics, 2023)
"The first Legion of Super-Heroes? Sort of. The United comes to the new Justice League for help because the biggest threat to the universe is on the loose, and all roads lead to... Superman. All this, and Aquaman has some surprising news. As the Justice League heads to deep space, following the trail of the most dangerous new criminal in all the galaxy. The biggest threat to the United Planets is on the loose, and no one in the cosmos is safe. Meanwhile, on Earth, Checkmate breaks into the Hall of Justice looking for clues to Black Canary's secret affiliation. What secret affiliation, you ask? It's a secret, duh! All this, and Black Adam declares himself leader of the League"--